P-375 Optimising vaginal biospecimen collection. (30th June 2022) - Turner, F; Drury, J; Goodfellow, L; Hill, C; Baxter, H; Milanova, V; Drakeley, A; Hapangama, D; Tempest, N
Abstract: Study question: Are menstrual tampons an acceptable and comparable method to lower vaginal swabs (LVS) for analysing the vaginal microbiome in non-pregnant women? Summary answer: Tampons capture a higher bacterial load, volunteers are familiar with them, thus are well-accepted, and can be efficiently frozen at -20 °C prior to analysis. What is known already: The vaginal microbiome plays a key role in women's reproductive health. The application of investigating this niche allows a greater understanding of the impact of the vaginal microbiota in diverse reproductive disorders including infertility, recurrent miscarriage, spontaneous preterm birth and sexually transmitted infections. Fear and embarrassment related to physicians taking a traditional vaginal swab using a speculum results in many female genitourinary health appointments to be missed in the UK and recruitment challenges into vaginal microbiota research studies. Growing evidence suggests a menstrual tampon to be a superior alternative biospecimen collection device to a vaginal swab. Study design, size, duration: This was a prospective, cross-sectional observational study. Twenty-one healthy volunteers (average age 30 years) were recruited over a period of 6 weeks at the Centre for Women's Health Research, University of Liverpool, an academic, tertiary referral centre. Participants/materials, setting, methods: The volunteers consented to wearing a tampon for 20 minutes, taking 2 LVS and completing an acceptability questionnaire. Samples were halved for immediate processing and freezing at -20 °C for 2-4 weeks. Real-time PCR using Femoflor-16 was carried out to identify microorganisms present in vaginal microbiota. Microbiota was classified by total bacterial mass and relative abundance of lactobacillus species. Statistical analysis was carried out using GraphPad PRISM 5, Microsoft Excel 2019 and IBM SPSS Statistics 27. Main results and the role of chance: Of the 84 samples, four had insufficient material for the purpose of analysis. Three of these were LVS samples and the fourth was a frozen tampon sample. Mean tampon total bacterial mass was higher for fresh and frozen samples versus the mean LVS total bacterial mass. The Femoflor algorithm gave identical vaginal microbiota characterisation between the fresh tampon and fresh LVS in 68.4% (13/19) of cases. 92% (12/13) samples with over 80% relative abundance of lactobacillus in the LVS also had over 80% relative abundance in the tampon. More discrepancy was seen between samples within the 20-80% and <20% relative abundance groups of lactobacillus in the LVS with 50% and 75% different classifications respectively. Importantly, only one case showed an LVS with lactobacillus >80% (normal) and a tampon with non-dominance of lactobacillus (<80%, dysbiosis). The questionnaires revealed that 90.5% of the volunteers highly rated using tampons (3 or more out of 5 on a Likert scale), with 52.4% rating tampon-use at 5/5. All participants (100%) stated that they would be happy to provide a tampon sample for clinical/research testing purposes in the future. Limitations, reasons for caution: This study included 21 healthy volunteers; this is not necessarily representative of the entire UK population, but the tampon and LVS from the same volunteer were consistently comparable before and after freezing. We used a multiplex PCR assay to target common vaginal bacteria, inevitably some bacteria have not been characterised. Wider implications of the findings: Self-collected tampons are suitable, well accepted biospecimen collection devices that may reduce barriers posed due to embarrassment, improve attendance in genitourinary medicine clinics and encourage participation in vaginal microbiota research. Freezing before processing reduces time and costs. A large study is necessary to ensure reproducibility and acceptability to patient population. Trial registration number: Not Applicable